An attitude to the physical culture of first-graders and their parents. - Bodnarchuk О.M; Zanevsky I.P (Kharkov National Pedagogical University, 2011)
The purpose of the work is the determination of the attitude of first-graders and their parents toward physical culture and sport. In experiment took part 92 first formers and their parents. There were determined in what measure first-graders are organised with participations in the sport sections, the dancing clubs, etc. The priorities of first-graders relative to spending of free time are discussed, as well as the point of view of their parents in regard to this. It is proved that 89 per cent of first formers and 93 per cent of their parents thought exercises of physical education and sport healthy.